Cost-Effectiveness of Nivolumab Plus Ipilimumab as First-Line Therapy in Advanced Non–small-cell Lung Cancer - Hao, Xuezhi; Shen, Aizong; Wu, Bin (Frontiers in Pharmacology, 2021)
Purpose: The effectiveness of nivolumab plus ipilimumab for advanced non-small cell lung cancer (NSCLC) has been demonstrated. Decisions have to be made about allocating healthcare resources. Economic evidence could support policy decisions to fund expensive interventions. The current analysis evaluated the cost-effectiveness of nivolumab plus ipilimumab in advanced NSCLC harboring no EGFR or ALK mutations. It is set in the context of the US and China, representing developed and resource-constrained settings, respectively. Patients and Methods: A Markov model consisting of three discrete health states was used to assess the cost-effectiveness of nivolumab plus ipilimumab versus chemotherapy. The key clinical data were derived from the CheckMate-227 trial, and the cost and health preference data were derived from the literature. Costs, quality-adjusted life-years (QALYs), incremental cost-effectiveness ratios (ICERs) and incremental net health benefits (INHBs) were calculated for the two strategies. Subgroup, one-way and probabilistic sensitivity analyses were performed. Results: In the US, nivolumab plus ipilimumab increased by 1.260 QALYs with an additional cost of 95,617 compared with the features of chemotherapy, which led to an ICER of 75,871 per QALY gained. INHB indicated that nivolumab plus ipilimumab treatment had a 99% probability of being cost-effective at the ICER threshold of 100,000/QALY in all subgroups. The results of sensitivity analyses revealed that the model outcomes were robust. In China, the ICER of nivolumab plus ipilimumab versus chemotherapy was 59,773/QALY, and the INHB was -1.972 QALY at the threshold of 27,351/QALY. Conclusion: Nivolumab plus ipilimumab treatment is a cost-effective option compared with chemotherapy for patients with advanced NSCLC harboring no EGFR or ALK mutations in the US. However, nivolumab plus ipilimumab is not a preferred option in China.